5(x-3)-2(x-7)=7-7(2x+6)
Va rog ajutatima::::
Răspunsuri la întrebare
Răspuns de
0
5(x-3)-2(x-7)=1(2x+6)/:5
X-3-2(x&7)=5:1*2x+6
X-1(x-7)=5•2x+6
X-1x-7=10x+6
2x-6=x/-6
2x=x/:x
2=x
Wowke:
ce logica ai folosit?
Răspuns de
1
5(x-3)-2(x-7)=7-7(2x+6)=
5x-15-2x+14=7-14x-42
3x-1=-35-14x
3x+14x=-35+1
17x=-34
x=
5x-15-2x+14=7-14x-42
3x-1=-35-14x
3x+14x=-35+1
17x=-34
x=
Alte întrebări interesante
Limba română,
9 ani în urmă
Engleza,
9 ani în urmă
Limba română,
10 ani în urmă
Matematică,
10 ani în urmă
Matematică,
10 ani în urmă